Pathophysiologic Mechanisms of Insulin Secretion and Signaling-Related Genes in Etiology of Polycystic Ovary Syndrome - Zahra Shaaban; Arezoo Khoradmehr; Amir Amiri-Yekta; Fariborz Nowzari; Mohammad Reza Jafarzadeh Shirazi; Amin Tamadon (Genetics Research)
Polycystic ovary syndrome (PCOS) is a common endocrinopathy in women. PCOS is characterized by anovulation, hyperandrogenism, polycystic ovaries, insulin resistance, and obesity. Despite the finding that the genetic origin of PCOS is well demonstrated in previous twin and familial clustering studies, genes and factors that can exactly explain the PCOS pathophysiology are not known. Objective(s). In this review, we attempted to identify genes related to secretion and signaling of insulin aspects of PCOS and their physiological functions in order to explain the pathways that are regulated by these genes which can be a prominent function in PCOS predisposition. Materials and Methods. For this purpose, published articles and reviews dealing with genetic evaluation of PCOS in women from peer-reviewed journals in PubMed and Google Scholar databases were included in this review. Results. The genomic investigations in women of different populations identified many candidate genes and loci that are associated with PCOS. The most important of them are INSR, IRS1-2, MTNR1A, MTNR1B, THADA, PPAR-γ2, ADIPOQ, and CAPN10. These are mainly associated with metabolic aspects of PCOS. Conclusions. In this review, we proposed that each of these genes may interrupt specific physiological pathways by affecting them and contribute to PCOS initiation. It is clear that the role of genes involved in insulin secretion and signaling is more critical than other pathways.